Feasibility Analysis of Residential Electrical Installations Over 15 Years Old Based on PUIL 2020 in Temuyuk Village, Bunut Hulu District - Kardo, Riki; Husin, Fitriah; Arsyad, M.Iqbal (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2025)
Electricity is a very important need and the most important economic resource for humans. One of the important factors in fulfilling electrical safety is the installation of electrical installations that meet the provisions and standards regulated in the 2020 General Requirements for Electrical Installations (PUIL) as a reference for installing electrical installations. This is the problem of this research, namely the level of feasibility of electrical installations and the causal factors. inadequacy of electrical installation. This research aims to determine the percentage of feasibility of electrical installations and determine the causes of unfeasible electrical installations. The method used is descriptive analytic. The sample in this study was Temuyuk Village, Bunut Hulu District with a power limitation of 450 VA -900 VA for 79 houses. The sampling technique uses proportional random sampling technique. Data collection techniques use observation, interviews and documentation. In this research, there are five references for feasibility parameters, namely: feasibility of equipment, feasibility of conducting cables, feasibility of installation safety (MCB), feasibility of input voltage and feasibility of insulation resistance. The results of the percentage of feasibility of electrical installations for households in Temuyuk Village, Bunut Hulu District over the age of 15 years were 77.22% feasible (amounting to 61 houses) and 22.78% not feasible (amounting to 18 houses).